Comparison of the effects of active, passive and mixed warm ups on swimming performance - Adams, S.; Psycharakis, S. G. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The aim of this paper was to compare the effects of an active (AWU), passive (PWU) and mixed warm up (MWU) on swimming performance.